2012
DOI: 10.1089/end.2012.0139
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Cystoscopy Findings in Patients Investigated for Profound Lower Urinary Tract Symptoms, Recurrent Urinary Tract Infection, and Pain

Abstract: Clinically relevant abnormalities were found in 11.5% of patients with pLUTS, rUTI, or pain, supporting recently published NICE guidelines recommending cystoscopy in patients with pLUTS or rUTI. Of the 17 patients who were investigated for pain, none was found to have clinically relevant abnormalities; further studies are needed to define the clinical utility of FC in these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Howles et al retrospectively investigated the diagnostic performance of flexible cystoscopy for 113 men and women with profound lower urinary tract symptoms, recurrent UTI, or pain . Because there is no female equivalent to the 2010 NICE guidelines for men with these conditions, the authors attempted to extrapolate guideline recommendations to a cohort of both men and women .…”
Section: Discussionmentioning
confidence: 99%
“…Howles et al retrospectively investigated the diagnostic performance of flexible cystoscopy for 113 men and women with profound lower urinary tract symptoms, recurrent UTI, or pain . Because there is no female equivalent to the 2010 NICE guidelines for men with these conditions, the authors attempted to extrapolate guideline recommendations to a cohort of both men and women .…”
Section: Discussionmentioning
confidence: 99%
“…NICE have developed guidelines for the investigation of these symptoms in men [14]. A study of British men found that the incidence of bladder cancer in these patients was low (0.9%) [15]. …”
Section: Are There Gender Differences In Referral Patterns?mentioning
confidence: 99%
“…In the mentioned study, cystoscopy was recommended for patients with profound lower urinary tract symptoms and recurrent UTI. In addition, the frequency of urinary tract disorders was significantly higher in males (17).…”
Section: Discussionmentioning
confidence: 90%
“…In another study by Howles et al, the diagnostic performance of flexible cystoscopy in patients with profound lower urinary tract symptoms, recurrent urinary tract infection, and pain were examined retrospectively (17). Thir-teen (11.5%) out of 113 patients had significant cystoscopy findings, including bladder cancer (1), urethral stricture (9), and intravesical calculi (4).…”
Section: Discussionmentioning
confidence: 99%